Current issues and trends in special education research, technology, and teacher preparation - Obiakor, Festus E.; Bakken, Jeffrey P.; Rotatori, Anthony F. (Advances in special education ;, 2010)
"This is the second of two themed volumes addressing current issues and trends in special education. Volume 20 covers research, technology, and teacher preparation whilst volume 19 covered identification, assessment and instruction. The field of special education constantly changes as a result of legislation, new instructional formats and current research investigations. It can be difficult for general and special educators, school counselors and psychologists, administrators and practicing clinicians to keep up with these changes and be current in all areas relating to special education. The special education literature knowledge base should reflect these changes; however, there is no current resource that effectively and comprehensively does this. The purpose of "Current Issues and Trends in Special Education" is to fill this void, providing chapters written by active researchers and practitioners in their respective areas.